Does next-generation sequencing of cyst fluid improve management of pancreatic cystic neoplasms?. (3rd October 2017) - Aronsson, Linus; Andersson, Roland; Swahn, Fredrik; Ansari, Daniel
Abstract: Pancreatic cystic lesions represent a heterogeneous group of diseases ranging from benign to malignant lesions. They are increasingly being detected due to the widespread use of cross-sectional imaging. Their management is a challenge because it is often not possible to reliably discriminate between malignant and nonmalignant lesions using current imaging technology. Next-generation sequencing (NGS) has the ability of both whole genome and targeted sequencing at a low cost and from a limited amount of DNA. NGS of cyst fluid aspired by endoscopic ultrasonography-guided fine-needle aspiration provides a valuable tool in biomarker research and may in the future help improve diagnosis and management of pancreatic cystic lesions.